Cultivating the Unseen: Paʻakai and the Role of Practice in Coastal Care - Gina McGuire; Alexander Mawyer (Ethnobiology Letters, 2023)
This piece centers itself in paʻakai (seasalt) practices as providing a critical lens for an ethnoecology of the rural Puna coastline on the island of Hawaiʻi. Grounded by ethnographic engagement with ʻŌiwi (Native Hawaiian) tradition, interweaving moʻolelo (stories) from kūpuna (ancestors, elders) alongside contemporary praxis in Puna, Hawaiʻi Island, we explore the role of paʻakai gathering, limu (seaweed) provisioning, and offshore spring water collection in what we are calling coastal care—the reciprocal relationship of care between communities and coasts. Hawaiian cultural practices around paʻakai are a striking home for biocultural linkages including practitioners’ understandings of human and other-than-human wellbeing that exemplify the diversity of cultural dimensions tangibly present in coastal places. Highlighting the plurality of roles culture plays in the sustainable stewardship and wellbeing of coastal places and communities, this work contributes to ongoing discourses around the role of human dimensions in coastal conservation and management. Here we use water, pa‘akai, and limu to make visible what we call the “unseen realm” within contemporary conservation—the persistent blind spots around Indigenous and local culture(s) within conservation policy, planning, and enactment. Encouraging conservation and island sustainability scientists and practitioners to better engage with their blind spots, we identify the need for collaborative coastal management inclusive of ʻŌiwi practices and understandings of coastal care with implications for coastal studies in Hawai‘i and in other Indigenous contexts across Oceania.